ChemInform Abstract: Enhanced Luminescence of Novel Y2Zr2O7:Dy3+ Phosphors by Li+ Co‐Doping. Issue 14 (20th March 2013) - Du, Qingqing; Zhou, Guangjun; Zhou, Juan; Jia, Xiao; Zhou, Haifeng
Abstract Novel blue‐white Y2Zr2O7:Dy3+, Li+ phosphors are synthesized by the sol—gel combustion method starting with ZrO(Ac)2, Y(NO3)3, Dy(NO3)3, Li(NO3), NH4NO3, and citric acid (800 °C, 30 min).